Structure of the Mae On Depression, Chiang Mai province, based on gravity modelling and geological field observation: Implications for tectonic evolution of the Chiang Mai – Chiang Rai Suture Zone, Northern Thailand - Niti Mankhemthong (2020)
© 2019 Elsevier Ltd We propose a structural model for the tectonic evolution of the Mae On Depression area along the Chiang Mai-Chiang Rai Suture Zone (CMCRSZ). The study location is the central Mae On District, where a topographic depression is present that is continuous with the eastern margin of Chiang Mai rift basin. Yet volcanic exposures mapped in topographic lows indicate the depression has not developed as part of the syn-rift or post-rift basin with sediment fill. Terrestrial gravity was acquired to visualize the subsurface extent of the volcanic exposures, which are part of a mélange complex associated with the Sibumasu-Sukhothai Terrane collision during the Permo-Triassic Indosinian Orogeny. Gravity anomaly highs correspond to the asymmetrical trapezoid geometry of a relatively dense volcanic block with a thickness of around 750–900 m, overlain by lower density units comprising carbonate and pelagic formations, interpreted as typical ocean plate stratigraphy associated with a volcanic seamount. Gravity gradient analysis fits with the geological interpretation of a klippe of Mae Tha Formation, derived from the western margin of the Sukhothai Terrane in thrust contact with the CMCRSZ mélange. The structural interpretation of the gravity modelling provides important constraints on the tectonic contacts along the CMCRSZ that fits the eastward subduction model of the Palaeo-Tethys beneath the Sukhothai Terrane. The Mae On Depression is one of the best localities in Northern Thailand for demonstrating the thickness and extent of blocks of Palaeo-Tethys volcanics associated with carbonates, which are interpreted as representing former seamounts.